The ethics of the special ranking for pregnancy in tennis. Issue 1 (2nd January 2020) - Torres, Cesar R.; Lopez Frías, Francisco Javier
ABSTRACT: In this paper, we provide a normative analysis of the Women's Tennis Association revised policy on maternity leave, which is regulated by its special ranking rule. To do so, we first explore how the revised policy functions when probed in relation to the nature of competitive sport. Then, we examine the revised policy through the lens of the literature on maternity discrimination. We argue that, when compared to its previous formulation, the revised special ranking rule is morally defensible because it better protects female players' interest in being able to combine their professional careers and their personal lives. However, we also identify several pronounced vulnerabilities and criticisms to the revised policy.